2018
DOI: 10.1177/2474126418785824
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complication Rates in 23- vs 25-Gauge Pars Plana Vitrectomy

Abstract: The purpose of this study was to compare rates of clinically significant complications between 23-and 25-gauge pars plana vitrectomy (PPV) in vitreoretinal surgery. Methods: Demographics, PPV indication, and surgical complications were reviewed. Patients with prior PPV or other retina surgery; cases requiring silicone oil removal, keratoplasty, or glaucoma valve implant; patients <18 years old; or patients with <4 months of follow-up were excluded. Comparative and descriptive statistics were used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Byeon et al followed eyes after 25-gauge vitrectomy and observed retinal detachments in 6% of cases [ 20 ]. A large retrospective chart review of 579 eyes that underwent vitrectomy for different indications showed a retinal detachment rate of 8.2% in the 23-gauge and 4.2% rate in the 25-gauge group [ 21 ]. In a study of 92 patients conducted by Gupta et.…”
Section: Discussionmentioning
confidence: 99%
“…Byeon et al followed eyes after 25-gauge vitrectomy and observed retinal detachments in 6% of cases [ 20 ]. A large retrospective chart review of 579 eyes that underwent vitrectomy for different indications showed a retinal detachment rate of 8.2% in the 23-gauge and 4.2% rate in the 25-gauge group [ 21 ]. In a study of 92 patients conducted by Gupta et.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports on the rate of intraoperative and postoperative complications among the three main MIVS gauge systems, with most data showing similar safety profiles [ 13 , 14 ]. A recent comprehensive review comparing 23- and 25-gauge pars plana vitrectomy (PPV) surgery showed an increased rate of overall adverse events for the 23-gauge system [ 15 ]. Additionally, 25- and 27-gauge PPV have shown increased intraocular pressure (IOP) stability and decreased conjunctival trauma compared to 23-gauge PPV [ 16 , 17 ].…”
Section: Administration Routesmentioning
confidence: 99%